Isolation and Homology Analysis of Alanine Aminotransferase Gene of Barley, Foxtail Millet, Cucumber, and Tomato - Atmitri Sisharmini; Aniversari Apriana; Tri Joko Santoso; Bambang Sapta Purwoko; Nurul Khumaida; Kurniawan Rudi Trijatmiko (Jurnal AgroBiogen, 2020)
Overexpression of alanine aminotransferase (AlaAT) gene can improve nitrogen use efficiency (NUE) in plants. The previous isolated AlaAT genes cannot be freely applied to generate NUE plants due to IPR restriction. Therefore, isolation of the gene from targeted monocot and dicot plants is necessary. The objectives of this study were to isolate AlaAT genes from barley, foxtail millet, cucumber, and tomato and analyze their homology to other isolated AlaAT genes in sequence databases (gene bank). Total RNA was isolated from roots of barley, foxtail millet, cucumber, and tomato, and then converted into cDNA using reverse transcription method. The cDNA was then cloned into pGEM®-T Easy plasmid and the verified clones were sequenced. The amino acid sequences were analyzed for their homologies using Clustal Omega software and phylogenetic tree was constructed. The results showed that the amino acids of AlaAT gene from barley was different from AlaAT genes of tomato and cucumber with homology level less than 80%. Phylogenetic tree predicted that AlaAT genes clustered into three groups with AlaAT genes of foxtail millet and barley clustered in one group together with other monocots in group I. AlaAT genes derived from dicots clustered into two groups in which AlaAT gene of tomato clustered in group II, while that of cucumber was in group III. The identity differences of AlaAT gene of tomato and that of cucumber as well as the estimates of the same enzymatic functions can open up enormous opportunities in genetic engineering research for the development of NUE rice.